Securing Microservice CICD Pipelines in Cloud Deployments through Infrastructure as Code Implementation Approach and Best Practices - Singh, Amarjeet; Aggarwal, Alok (Journal of Science & Technology, 2022)
With the exponential growth of microservices architecture and the ubiquitous adoption of continuous integration/continuous deployment (CI/CD) practices in cloud environments, ensuring the robust security of the entire pipeline becomes increasingly critical. Infrastructure as Code (IaC) emerges as a pivotal approach to automate and manage infrastructure deployments, presenting an unparalleled opportunity to seamlessly integrate security measures throughout the development lifecycle. This paper offers a comprehensive analysis of the intricate security challenges inherent in microservice CI/CD pipelines and proposes a meticulously crafted implementation approach leveraging the power of IaC to fortify the security posture. By meticulously examining a myriad of security considerations and distilling best practices, this research endeavors to furnish practical insights into safeguarding microservice deployments in the dynamic landscape of cloud environments, where agility and security converge at the forefront of modern software engineering practices.
Keywords: Microservices; IAC; AWS; Microservices Security; SAST; Micro-services